Dual-Band Circularly Polarized Shared-Aperture Vivaldi MIMO Antenna With Linear-to-Circular Polarizer for 5G and 6G Communication - Ikram, Muhammad (2025)
The upcoming sixth-generation (6G) communication system is set to operate in the sub-THz band, which could provide substantially higher communication capacity. Meanwhile, the fifth-generation (5G) systems have already started to operate in the millimeter-wave (mm-Wave) bands. Therefore, dual-band antennas, which can operate for both 5G and 6G bands simultaneously, with circularly polarized (CP) radiation, are attractive for future wireless communication. However, achieving dual-band CP radiations, at frequencies as high as 100 GHz, is quite challenging. In this work, a novel dual-band, CP, eight-port multiple-input-multiple-output (MIMO) antenna is presented. The proposed CP MIMO configuration comprises an orthogonally placed four-element shared-aperture Vivaldi antenna and a linear-to-dual-circular polarization (LDCP) converter, operating at the frequencies of 40 GHz (5G mm-Wave band) and 110 GHz (6G sub-THz band). The shared-aperture Vivaldi antenna, proposed as the excitation source for the LDCP converter, demonstrates high gain, compact size, and endfire linearly polarized (LP) radiation for dual-wideband operation (5G/6G). The designed dual-band LDCP converter has a compact unit cell size ( 0.16? at 40 GHz) and works for both horizontal and vertical polarizations. The fabricated prototype demonstrates a measured left-hand circular polarized (LHCP) bandwidth (BW) from 39 to 45 GHz (14.2%) for the 5G band and a right-hand circular polarized (RHCP) BW from 98 to 110 GHz (11.5%) for the 6G band. For the first time, we demonstrate a dual-band, dual-CP eight-port MIMO antenna with polarization (LHCP/RHCP) and spatial (30° incidence angle difference) diversity at the 5G/6G bands, making it a suitable candidate for future integrated 5G/6G communication systems.